Community initiatives for well‐being in the United Kingdom and their role in developing social capital and addressing loneliness: A scoping review - Stephanie Tierney; Rosie Rowe; Emily L Connally; Nia W Roberts; Kamal R Mahtani; Jordan Gorenberg (Wiley, 2024)
Abstract Introduction Loneliness can have a negative impact on people's physical and psychological well‐being; building social capital is a potential means of addressing this connection. Community initiatives (e.g. groups, clubs, neighbourhood activities) may be a route that enables people to build social capital to tackle loneliness. Understanding what is known, and where gaps in knowledge exist, is important for advancing research on this topic. Methods A scoping review was undertaken to explore the question - What community initiatives, with a focus on well‐being, have been evaluated in the United Kingdom that include information about social capital and loneliness? Four databases (Medline, CINAHL, ASSIA and Embase) were searched for relevant research papers. References were screened by two researchers to identify if they met the review's inclusion criteria. Data were summarised as a narrative and in tables. Results Five papers met the review's inclusion criteria. They all used qualitative methods. Findings suggested that social capital could be developed through creating a sense of trust, group cohesion and reciprocity among participants in the community initiatives. This connection enabled people to experience a sense of belonging and to feel they had a meaningful relationship with others, which appeared to alleviate feelings of loneliness. Conclusion More research is warranted on the review topic, including studies that have employed quantitative or mixed methods. Clarity around definitions of social capital and loneliness in future research is required. Engagement with community initiatives can provide a formalised route to help people develop connections and counteract limitations in their social networks. However, individuals may be wary about attending community initiatives, needing support and encouragement to do so. Social prescribing link workers are one means of motivating people to access groups, events or organisations that could improve their well‐being.